Application of hydrolases and probiotic Pediococcus acidilactici BaltBio01 strain for cereal by-products conversion to bioproduct for food/feed. (17th February 2018) - Bartkiene, Elena; Bartkevics, Vadims; Krungleviciute, Vita; Juodeikiene, Grazina; Zadeike, Daiva; Baliukoniene, Violeta; Bakutis, Bronius; Zelvyte, Rasa; Santini, Antonello; Cizeikiene, Dalia
Abstract: The aim of this study was to apply the enzymatic treatment and fermentation by Pediococcus acidilactici BaltBio01 strain for industrial cereal by-products conversion to food/feed bioproducts with high amount of probiotic lactic acid bacteria (LAB). LAB propagated in potato media and spray-dried remained viable during 12 months (7.0 log10 cfu/g) of storage and was used as a starter for cereal by-products fermentation. The changes of microbial profile, biogenic amines (BAs), mycotoxins, lactic acid (L + /D − ), lignans and alkylresorcinols (ARs) contents in fermented cereal by-product were analysed. Cereal by-products enzymatic hydrolysis before fermentation allows to obtain a higher count of LAB during fermentation. Fermentation with P. acidilactici reduce mycotoxins content in fermented cereal by-products. According to our results, P. acidilactici multiplied in potato juice could be used for cereal by-products fermentation, as a potential source to produce safer food/feed bioproduct with high amount of probiotic LAB for industrial production.